A higher maternal choline intake among third‐trimester pregnant women lowers placental and circulating concentrations of the antiangiogenic factor fms‐like tyrosine kinase‐1 (sFLT1). Issue 3 (29th November 2012) - Jiang, Xinyin; Bar, Haim Y.; Yan, Jian; Jones, Sara; Brannon, Patsy M.; West, Allyson A.; Perry, Cydne A.; Ganti, Anita; Pressman, Eva; Devapatla, Srisatish; Vermeylen, Francoise; Wells, Martin T.; et al.
Abstract : This study investigated the influence of maternal choline intake on the human placental transcriptome, with a special interest in its role in modulating placental vascular function. Healthy pregnant women ( n =26, wk 26–29 gestation) were randomized to 480 mg choline/d, an intake level approximating the adequate intake of 450 mg/d, or 930 mg/d for 12 wk. Maternal blood and placental samples were retrieved at delivery. Whole genome expression microarrays were used to identify placental genes and biological processes impacted by maternal choline intake. Maternal choline intake influenced a wide array of genes ( n =166) and biological processes ( n =197), including those related to vascular function. Of special interest was the 30% down‐regulation ( P =0.05) of the antiangiogenic factor and preeclampsia risk marker fms‐like tyrosine kinase‐1 ( sFLT1 ) in the placenta tissues obtained from the 930 vs. 480 mg/d choline intake group. Similar decreases ( P =0.04) were detected in maternal blood sFLT1 protein concentrations. The down‐regulation of sFLT1 by choline treatment was confirmed in a human trophoblast cell culture model and may be related to enhanced acetylcholine signaling. These findings indicate that supplementing the maternal diet with extra choline may improve placental angiogenesis and mitigate some of the pathological antecedents of preeclampsia.—Jiang, X., Bar, H. Y., Yan, J., Jones, S., Brannon, P. M., West, A. A., Perry, C. A., Ganti, A., Pressman, E., Devapatla, S., Vermeylen, F., Wells, M. T., and Caudill, M. A. A higher maternal choline intake among third‐trimester pregnant women lowers placental and circulating concentrations of the antiangiogenic factor fms‐like tyrosine kinase‐1 (sFLT1). FASEB J. 27, 1245–1253 (2013). www.fasebj.org